426 PREVALENCE OF, AND RISK FACTORS FOR, DEMENTIA IN ADULT OUTPATIENT REFERRALS TO A REGIONAL REFERRAL HOSPITAL IN ARUSHA, TANZANIA. (14th June 2021) - Roe, C; Safic, S; Mwaipopo, L; Dotchin, C; Klaptocz, J; Gray, K; Joseph, M; Walker, R
Abstract: Introduction: The global burden of dementia is increasing, with the greatest increase predicted to occur in sub-Saharan Africa (SSA). Despite this there are limited previous data on the prevalence of, and risk factors for, dementia in SSA. This study aimed to estimate the prevalence of dementia, and investigate its associations, in those aged 60 years and older attending the outpatient department of Mount Meru Hospital in northern Tanzania. This is the first hospital-based outpatient dementia prevalence and risk factors study to be conducted in an east African population. Methods: This was a one-phase cross-sectional study. Adults aged 60 years and over attending medical outpatients were screened for dementia using The Identification and Intervention for Dementia in Elderly Africans cognitive screening tool. Those who scored ≤9 were clinically assessed using the DSM-IV criteria. Demographic, medical comorbidity and lifestyle information were collected during a clinical assessment. Results: Prevalence of dementia was 5.0% (95% confidence interval: 3.7–6.3). Binary logistic regression found female sex (odds ratio (OR) = 2.778), having no formal education (OR = 6.088), quantity of alcohol consumption (units/week) (OR = 1.080), uncorrected visual impairment (OR = 4.260), body mass index <18.5 kg/m2 (OR = 6.588) and stroke (OR = 15.790 with wide 95% confidence interval (3.48–74.475)) to be significantly, independently associated with dementia. Conclusions: The prevalence of dementia in this population is lower than previously reported community-based rates in Tanzania, and similar to those in high-income countries. This is the first time the association between uncorrected visual impairment and dementia has been reported in SSA. Other associations identified are in keeping with previous literature. Further research on the management of dementia and its risk factors, and the support and education of carers and patients in east African populations is required.